Stop-Motion Video as Media of Teaching Theme-Based Vocabulary for Elementary Students - Muhammad Arif Sanjaya (FIP Unimed, 2020)
This article presents a procedure of developing an attractive stop-motion video as media of teaching theme-based vocabulary for elementary students. Stop-motion video is typically a product of technology-based media or known as multimedia which is designed and developed with technology integration. The media is proposed to be utilized to teach theme-based vocabulary for elementary students in the second grade. Theme-based vocabulary deals with a list of words referred to such specific themes as family members, occupations, favorite foods, favorite drinks, and public places. The media hopefully will attract students’ intention to learn English vocabularyand ease teachers in teaching theme-based vocabulary. Related theories about multimedia, stop-motion video, teaching theme-based vocabulary, and also steps of media development are discussed.Key Words: multimedia, stop-motion video, teaching theme-based vocabulary